Smiley’s «A thousand acres»: American adaptation of W. Shakespeare’s «The tragedy of King Lear» - Aliakseyenka, Yanina A. (Journal of the Belarusian State University. Philology, 2023)
The article deals with the specifics of the reception of W. Shakespeare’s «The tragedy of King Lear» in J. Smiley’s «A thousand acres». The current importance and theoretical significance of the research is explained by the need to systematise the achievements of the literary process at the turn of the 20th–21st centuries, to identify modern trends in the revision of the playwright’s legacy in the USA. The writer adapts the pretext to American reality, keeping the plot and the main characters of the play recognisable. The centre of the narrative shifts, allowing to hear the female version of events. In accordance with the main problem-thematic aspects of the novel, elements of feminist and ecological (united by the ideas of ecofeminism), socio-critical, psychological and philosophical prose are distinguished. The foreign author’s literary works become a part of the national culture of the USA and one of the factors which affect the process of nationogenesis.
Keywords: national identity; national character; pastoral myth; reception; modern adaptation; Shakespeare’s plot; ecofeminism